The relationship between preschool teachers’ self-efficacy beliefs and their teaching attitudes - Kamil Arif Kırkıç; Fatma Çetinkaya (Institute of Advanced Engineering and Science, 2020)
This study examined the relationship between preschool teachers’ selfefficacy beliefs and their teaching attitudes. In the study, it was considered whether preschool teachers’ self-efficacy beliefs and their teaching attitudes change in terms of certain variables. The research was carried out using a correlational survey model. The target population of the study is the preschool teachers working in Küçükçekmece district, İstanbul Province, in the 2017-2018 academic year. The working group consists of 264 preschool teachers working at the schools in said district. The following assessment instruments were used in the research: “Personal Information Form,” “Preschool Teachers’ Self-efficacy Beliefs Scale,” to identify preschool teachers’ self-efficacy beliefs and ‘Preschool Teachers’ Teaching Attitudes Scale’ to determine the teachers’ attitudes. The obtained data were analyzed using Pearson multiplication moment correlation analysis, and Regression analysis was performed to determine the level of self-efficacy beliefs of preschool teachers affecting teaching attitudes. Preschool teachers were found to have full self-efficacy beliefs in the teaching-learning process, communication skills, planning, and regulation of learning environments and classroom management, and firm self-efficacy beliefs in family participation. Teachers’ attitudes of preschool teachers were found to be democratic at the highest level, followed by autocratic and laissez-faire at the lowest level. As a result of the regression analysis made to determine the level of the effect of self-efficacy beliefs of preschool teachers on their teaching attitudes, the learning and teaching process positively predicts democratic teaching attitudes and negatively predicts laissez-faire attitudes.